KYŌGEN, THE JAPANESE COMEDY OF CRAZY WORDS AND DELL’ARTE COMEDY. - Zalewska, Anna (Porównania, 2016)
Kyōgen, a form of Japanese comic theater, was created and developed alongside Noh theater and in the beginnings it was mostly improvised on stage. Later, the actors started to write down whole texts of kyōgen pieces. In this article the language of kyōgen drama is discussed, especially some of the frequently used elements, like the phrases used by the main character to introduce himself in the beginning, phrases used as a reaction to the words of other actors or phrases and even full sentences repeatedly used in many dramas in certain situations. Although until the 19TH century Japanese theater was functioning without any contact with European theater, some resemblances can be noticed between kyōgen and Italian commedia dell’arte. These resemblances and differences are also discussed in the article.